2020
DOI: 10.4103/jpi.jpi_10_20
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning to Estimate Human Epidermal Growth Factor Receptor 2 Status from Hematoxylin and Eosin-Stained Breast Tissue Images

Abstract: Context: Several therapeutically important mutations in cancers are economically detected using immunohistochemistry (IHC), which highlights the overexpression of specific antigens associated with the mutation. However, IHC panels can be imprecise and relatively expensive in low-income settings. On the other hand, although hematoxylin and eosin (H&E) staining used to visualize the general tissue morphology is a routine and low cost, it does not highlight any specific antigen or mutation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 26 publications
(24 reference statements)
0
31
0
Order By: Relevance
“…While much effort continues to perpetuate the successful application of deep learning models to digital pathology, relatively few efforts have been made to connect histopathology to molecular markers such as gene mutations, gene transcripts and proteins. Recent studies have shown that deep learning can identify and localize areas of tissue correlated with specific mutations in the breast [5] , [6] , [7] , lung [8] , and liver [9] cancers; predict microsatellite instability in colorectal [10] and gastrointestinal tumours [11] ; and predict tumour mutational burden in lung [12] and liver [13] cancers. The interest in predicting such signatures of disease stems from the downstream effects on phenotypes – particularly changes in gene expression – which in turn drives research towards particular targeted therapies [14] and informs clinical decisions [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…While much effort continues to perpetuate the successful application of deep learning models to digital pathology, relatively few efforts have been made to connect histopathology to molecular markers such as gene mutations, gene transcripts and proteins. Recent studies have shown that deep learning can identify and localize areas of tissue correlated with specific mutations in the breast [5] , [6] , [7] , lung [8] , and liver [9] cancers; predict microsatellite instability in colorectal [10] and gastrointestinal tumours [11] ; and predict tumour mutational burden in lung [12] and liver [13] cancers. The interest in predicting such signatures of disease stems from the downstream effects on phenotypes – particularly changes in gene expression – which in turn drives research towards particular targeted therapies [14] and informs clinical decisions [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other AI analyses have been performed for scoring or predicting the expression of biomarkers, such as HER2, Ki-67, estrogen receptor (ER) or progesterone receptor (PgR) [44][45][46][47], and assisting in identi cation of lymph node metastasis [48] or tumor-associated stroma [49]. However, these analyses are not directly related to the pathological diagnosis of complicated breast lesions.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Anand et al, HER2 overexpression was predicted from H&E-stained histopathology slides with an AUC of 0.76 on an independent test set from the TCGA [57]. Three separate neural networks were used in the approach described in this study.…”
Section: Predicting Gene Expression and Hormone Receptor Statusmentioning
confidence: 99%